FILSAFAT KEHENDAK SCHOPENHAUER DAN SIFAT QANA’AH SEBAGAI LANDASAN GAYA HIDUP MINIMALIS - Arifin, Jainul; Sofyan, Nurul Hikmah; Pujiono, Imam Prayogo (UIN Raden Mas Said Surakarta, 2024)
Consumerism often promises or measures one’s happiness through the ownership of things. In fact, the happiness obtained from material possessions is only temporary . This research aims to study how the theory of